The Role of The Basic Sector In The Regional Natural Income In Makassar City - Mapparenta Mapparenta; Aryati Arfah (Program Pascasarjana STIE Amkop Makassar, 2021)
Abstract This study aims to determine the sectors that are included as the base sector in Makassar City and to determine the magnitude of the influence of the manufacturing industry base sector, the construction sector, the wholesale and retail trade sector; repair of cars and motorcycles, as well as the information and communication sector on Regional Original Income in Makassar City. The data collection technique used in this research is the documentation technique. The data sources are secondary data obtained from the Regional Finance and Assets Agency of South Sulawesi Province and the Central Statistics Agency of Makassar City. Furthermore, the method used to answer the problems in this research is Location Quotient (LQ) analysis and simple regression analysis. The results of this study indicate that there are 11 sectors identified as the base sector in Makassar City, namely the manufacturing industry sector; water supply, waste management, waste and recycling; construction; wholesale and retail trade, repair of cars and motorcycles; provision of accommodation and food and drink; information and communication; financial and insurance services; company services; Education services; health services and social activities as well as other services with an average value of LQ more than 1. By using a simple regression model, it is obtained that the manufacturing sector, the construction sector, the wholesale and retail trade sector; Car and motorcycle repairs, as well as the information and communication sector have a positive and significant impact on Makassar City's PAD Keywords: PAD; PDRB; Basic Sector.